A new approach for istijrar valuation under stochastic volatility - Bayram, Kamola; Ganikhodjaev, Nasir (Islamic Business School, UUM, Kedah, 2014)
By employing VECM, Indonesia denotes that monetary policy shock in the short term stimulates significant shocks in the long term, whereas Malaysia experienced a stability trend showed by soft movement in the short term. As for Sudan, by employing VAR since no cointegration, it has a similar pattern with that of Malaysia indicated by IRF result. The short term analysis shows that monetary policy shock would lead to stability in the long run, although it shocked temporary except for exchange rate, which is set up to be resilient for any shock and stable in the short term as well as long term.